IMPLEMENTATION OF THE WEIGHTED PRODUCT METHOD RECIPIENTS OF THE REGIONAL OPERATIONAL ASSISTANCE PROGRAM (BOSDA) FOR EDUCATION EARLY CHILDHOOD - Sitta Ayu Anggraini; William Ramdhan; Masitah Handayani (Informatika, Universitas Jenderal Soedirman, 2022)
One of the government's efforts in equitable distribution of education is to launch the PAUD Regional Operational Assistance (BOSDA) program by providing financial assistance for each PAUD with underprivileged students. This Regional Operational Assistance (BOSDA) aims to reduce the cost of education for underprivileged children, so that they can obtain early childhood education services that can optimally foster, grow, and develop the full potential of early childhood. The problem that occurs is the Determination of Regional Operational Assistance Recipients (BOSDA) which is not optimal and not right on target. The purpose of this research is to facilitate the UPT employees of the Education Office in determining the recipients of the Regional Operational Assistance (BOSDA) program with the right decision results. Therefore, the UPT Department of Education requires the right technology to assist employees in determining the recipients of PAUD Regional Operational Assistance (BOSDA). In achieving the research objectives, the analysis used is data analysis with quantitative methods which is a data analysis used if the conclusions obtained can be proven by numbers and also in the calculation of formulas that have to do with research analysis. The calculation process uses the WP method, so that the results of the assessment that have been carried out go through many calculation processes, ranging from weighting the values ​​of all criteria and determining the value to getting a candidate for PAUD Regional Operational Assistance (BOSDA) at the UPT of the Buntu Pane District Education Office.